2015
DOI: 10.1016/j.clinbiomech.2015.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of vaulting strategy during locomotion of individuals with transfemoral amputation on slopes and cross-slopes compared to level walking

Abstract: Vaulting seems to be widely used by patients with transfemoral amputation in daily living situations. The number of patients using vaulting increased with the difficulty of the walking situation. Results also suggested that patients could dose the amount of vaulting according to gait environment to secure prosthetic toe clearance. During rehabilitation, vaulting should also be corrected or prevented in daily living tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Furthermore, they concluded that vF 2 values of an amputated limb decreased along with an increase of gait velocity. Lower vGRF values in the intact limb in the final support phase could occur as an adaptive mechanism to increase the foot clearance of the prosthetic foot, otherwise also known as the vaulting [ 13 ]. The results obtained in this research, when compared with those obtained by different authors, showed that vF 1 , vF 3 , and a-pF 1 GRF of the intact limb were identical for healthy people, while the values for the amputated limbs were much smaller [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they concluded that vF 2 values of an amputated limb decreased along with an increase of gait velocity. Lower vGRF values in the intact limb in the final support phase could occur as an adaptive mechanism to increase the foot clearance of the prosthetic foot, otherwise also known as the vaulting [ 13 ]. The results obtained in this research, when compared with those obtained by different authors, showed that vF 1 , vF 3 , and a-pF 1 GRF of the intact limb were identical for healthy people, while the values for the amputated limbs were much smaller [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged asymmetrical loading was found to be a predictor of atrophy in tight stump muscles, overloading, and degenerative changes [ 11 ]. Patients with TFA develop compensatory strategies in order to decrease asymmetry, such as the vaulting strategy or hip hiking [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…To cope with the loss of functionality of prosthetic joints compared to physiologic joints, people with lower limb amputations often modify the kinematics of their contralateral or residual limbs, which results in gait deviations, such as vaulting or pelvic hiking. 14 These deviations could be quantified through biomechanical parameters derived from motion capture systems, but the use of such techniques in a clinical environment cannot be considered due to the complexity of the instrumentation and processing required. Thus, some authors have focused on analyzing the impact of gait deviations on global parameters such as gait asymmetry between prosthetic and contralateral limbs.…”
Section: Introductionmentioning
confidence: 99%
“…The prosthetic side showed higher values, particularly in the case of TO detection during RD as shown in Table III. This could be due to system errors such as improper placement of the footswitches, movement of the insole inside the shoe during ambulation, variation in the kinematics of the transfemoral amputee compared to able-bodied subjects and also prosthesis performance [26]. In addition, subject based constraints such as knee-ankle adaptability, particularly in the case of ramp activities and the use of these prosthetics for relatively short periods of time (each prosthetic leg was used for a week or two before the experiment) could also be potential explanations for the observed high TD values.…”
Section: Lack Of Proper Tomentioning
confidence: 99%